(untitled) (Homoeopathy for All, 2024)
Appetite is a vital indicator of overall health, reflecting the body’s efficiency in utilizing nutrients. A healthy appetite signifies proper bodily function, while a lack of appetite can signal various health issues. A balanced appetite ensures essential nutrient intake, reflecting internal harmony and readiness for engagement. Controlled by hormonal, neural, and psychological factors, appetite regulation involves hormones like ghrelin and leptin1, alongside insulin2, with the hypothalamus and brainstem integrating these signals for energy balance.